Methods and adaptations required to perform small-animal MRI scanning using a large bore clinical MRI - Saleh, Muhammad G (Department of Human Biology, 2016)
Small-animal imaging has been widely implemented to study succession of disease, therapeutic treatments and the effects of environmental insults. The gold standard noninvasive technique for following progression of heart failure in small-animal models is magnetic resonance imaging (MRI). The aim of this project was to adapt a clinical MRI system to perform small-animal cardiac MRI. The first part of the thesis describes the adaptations required, which included design and construction of a small-animal radiofrequency (RF) coil, physical support (cradle), a core body temperature regulation system, and optimization of pulse sequences. The system was validated using a phantom and in-vivo in 5 healthy rats. The signal-to-noise ratio (SNR) in the phantom was 91% higher using the small-animal coil compared to the standard head coil. SNRs of 7 ± 2 and 18.9 ± 0.6 were achieved in myocardium and blood, respectively, in healthy rats and MR left ventricular mass (LVM) was highly correlated with (r=0.87) with post-mortem mass. In the second part of the study, left ventricular remodeling (LVR) was investigated in a nonreperfused model of myocardial infarction (MI) in 5 sham and 7 infarcted rats. Rats were scanned at 2 and 4 weeks post surgery to allow for global and regional functional and structural analyses of the heart. Images were of sufficient quality to enable semi-automatic segmentation using Segment. Significant increase in end-systolic volume (ESV) was observed in MI rats at 2 weeks post surgery. At 4 weeks post surgery, end-diastolic volume (EDV) and ESV of MI rats were significantly higher than in sham rats. Ejection fraction (EF) of MI rats dropped significantly at 2 weeks and a further significant drop was observed at 4 weeks indicating contractile dysfunction. Wall thickness (WTh) analyses in MI rats at 4 weeks revealed significant reduction in end-diastolic (ED) wall thickness in the anterior region due to necrosis of myocytes. In the posterior region, WTh was significantly higher due to LV hypertrophy. At end-systole (ES), the MI rats revealed significant decrease in WTh in the anterior and lateral regions. MI rats suffered reduction in systolic wall thickening in all regions of the heart, indicating global contractile dysfunction.